064 False positive RT-QuIC test for creutzfeldt jakob disease in dementia with status epilepticus. (23rd August 2021) - Wijesinghe, Rajiv; Anderson, Craig; Welgampola, Miriam; Stehmann, Christine; Collins, Steven; Spring, Penelope
Abstract : We present the case of a 72-year-old woman with likely false positive tests for Creutzfeldt Jakob disease (CJD). She had a background of focal epilepsy and dementia, related to previous alcohol abuse and head trauma. On her initial presentation in October 2019, she was drowsy with continuous left sided focal motor seizures. An EEG demonstrated continuous periodic lateralised epileptiform discharges (PLEDs) arising from the right temporal region, consistent with status epilepticus. She was commenced on levetiracetam and subsequently lacosamide, with seizure resolution over 12 days. Despite control of her seizures, she remained significantly cognitively impaired. A cerebral MRI demonstrated asymmetric cortical and thalamic diffusion restriction and the possibility of sporadic CJD was raised. A lumbar puncture revealed a normal total protein (0.4 g/L), a positive 14-3-3 protein but an undetectable tau protein. She was eventually discharged to a residential aged care facility, however returned to a different hospital in January 2020, obtunded with recurrent generalized seizures. Further results of her previous CSF examination were now available, revealing a positive RT-QuIC assay. However, a repeat MRI brain demonstrated resolution of the previous regions of diffusion restriction. Serial EEGs demonstrated continuous right temporal PLEDs which improved after the addition of sodium valproate. Repeat cognitive screening was markedly improved, however not quite reaching her 2019 baseline. We suggest that a false positive RT-QuIC test probably arose from status epilepticus in the context of significant pre-existing cerebral pathology. Excluding a pre-mortem diagnosis of CJD may be challenging in the setting of recurrent seizures.